Economic Survey of Latin America and the Caribbean 1989 - Economic Commission for Latin America; the Caribbean (United Nations, 1989)
The Economic Survey of Latin America and the Caribbean is issued annually by the Economic Development Division of the Economic Commission for Latin America and the Caribbean (ECLAC). It covers the economic situation in Latin America and provides a concurrent economic overview of the region.